Subject Card Files
This series consists of index cards. The cards give a profound and thorough documentation on Hungarian state agencies, ministries, organizations, institutions, associations, plants, factories, agricultural cooperatives, and hospitals, as well as on their leadership, personnel, and productivity. The information on the cards was continuously updated by extracting data from Hungarian and Western press, Hungarian monitoring materials, Information Items, and biographical files. Accruals not expected